A scale assessing doctor-patient communication in a context of acute conditions based on a systematic review. - Mélanie Sustersic; Aurélie Gauchet; Anaïs Kernou; Charlotte Gibert; Alison Foote; Céline Vermorel; Jean-Luc Bosson (PLoS ONE)
Background There is no validated generic tool to measure Doctor-Patient-Communication (DPC) in a context of acute conditions. Objective To create and validate such a scale in a real population. Materials and method We performed a systematic review of validated DPC scales available in English. From these, using a theoretical model based on a multidisciplinary approach, we selected pertinent items that met the inclusion criteria and included them in a simple questionnaire. This tool based on a synthesis of the literature was then validated in a prospective study in two hospital emergency departments. Results We found 22 pertinent questionnaires and scoring systems. From these, we extracted items and built a scale based on 15 questions with graded responses (Likert from 1 to 4). The mean time for questionnaire completion was 3 minutes. We included 189 adults and adolescents in the study and analyzed complete responses to the questionnaire by 149 patients, gathered over the phone one week after their consultation. The scale had high internal consistency (Cronbach's alpha = 0.89) and good external validity. Two questions were removed due to redundancy giving a scale based on 13 questions. Conclusions We have created an easy-to-use and validated generic questionnaire to assess DPC in a context of acute conditions, usable both in clinical research and in routine practice.